The consequences of ozone layer depletion on the health of Poles – a case study of skin melanoma - Wieteska, Stanisław; Jabłońska, Małgorzata (Olsztyn Economic Journal, 2019)
This article presents the results of the observation of cases of skin melanomas in Poland. Dermatologists raise the problem of increased sunlight penetration and the unreasonable use of solar radiation. This causes numerous cases of skin cancer. The aim of the article is to signal the threat posed by the depletion of the ozone layer in Poland. The article uses a research method based on an analysis of statistical data on skin cancers, supported by the available research in this area. Studies show that the incidence of skin cancer in Poland in 2007-2016 nearly doubled. Women are more prone than men to skin neoplasms. The mortality rate due to skin melanoma also increased dramatically. In the article, we point to the need of raising awareness of the hazards, and consider the coverage of treatment costs by life insurance as one of the options to protect the health of insured persons. We also raise the problem of prophylaxis on the basis of sunscreen cosmetic products.